1983
DOI: 10.1016/0968-0004(83)90099-3
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of neutral amino acid transport by amino acid availability in animal cells

Abstract: Animal cells regulate the activities of neutral amino acid transport Systems A and L to keep the intracellular supply of amino acids relatively constant. Transport System A activity increases dramatically in response to starvation of all the amino acids. Transport System L activity increases in response to starvation of a single substrate such as leucine. The mechanism of regulation appears to be different for Systems A and L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Earlier studies of pancreatic amino-acid transport established no regulatory role for islet hormones [4,5,8,20] or alloxan-induced diabetes [4], albeit glucose transport was stimulated by insulin in pancreatic acini [20]. In rat hepatocytes Na+-dependent neutral amino-acid transport via the hormone-sensitive System A [14,38] is elevated by insulin, glucagon and streptozotocin-induced diabetes, and activation of transport by diabetes may occur in vivo as a result of the hyperglucagonemia associated with the disease [2].…”
Section: Introductionmentioning
confidence: 98%
“…Earlier studies of pancreatic amino-acid transport established no regulatory role for islet hormones [4,5,8,20] or alloxan-induced diabetes [4], albeit glucose transport was stimulated by insulin in pancreatic acini [20]. In rat hepatocytes Na+-dependent neutral amino-acid transport via the hormone-sensitive System A [14,38] is elevated by insulin, glucagon and streptozotocin-induced diabetes, and activation of transport by diabetes may occur in vivo as a result of the hyperglucagonemia associated with the disease [2].…”
Section: Introductionmentioning
confidence: 98%
“…AIB, a non-metabolizable analogue of alanine, is frequently used to investigate alanine transport mechanism in eukaryotes (Lepley & Mukkada, 1983;Shotwell & Oxender, 1983). When Giardia cells were exposed to hypo-osmotic stress in the presence of external AIB, influx was observed.…”
Section: Effect Of Na+ Ci-and Inhibitors On Alanine Effluxmentioning
confidence: 99%
“…(1993) and Nygaard et al (1994) reported that Giardia contained an antiport for alanine influx and efflux, and this antiport showed a broad specificity for other amino acids structurally similar to Lalanine. A characteristic feature of this antiport was its inability to utilize AIB, a compound that is commonly used as a non-metabolizable analogue of alanine in investigation of alanine transport in other systems (Lepley & Mukkada, 1983;Shotwell & Oxender, 1983). On this basis, AIB was chosen to investigate the membrane transporter responsible for the acute response of Giardia to hypo-osmotic stress.…”
Section: Aib Transport Under Hypotonic Conditionsmentioning
confidence: 99%
“…Recently, transport systems A, ASC, and L have been characterized in Chinese hamster ovary (CHO) cells (2,34). Studies on system L regulation has also been carried out in these cells (24,33,(35)(36)(37) by using a temperature-sensitive leucyl-tRNA synthetase mutant, the CHO tsHl line. When this mutant is incubated at marginally permissive temperatures, a significant increase in leucine transport activity occurs, indicating that the cell responds to leucine limitation resulting from the defective leucyl-tRNA synthetase.…”
mentioning
confidence: 99%